2017
DOI: 10.1108/mrr-05-2016-0114
|View full text |Cite
|
Sign up to set email alerts
|

Middle management involvement in handling variable patient flows

Abstract: . His research deals with integration and coordination of a supply chain, and the intersection between logistics and different strategic management issues such as dynamic capabilities, the strategy formation process and business models. Structured Abstract:Purpose To explore the involvement of middle management in forming strategies to manage variable acute patient flows at a hospital. Design/methodology/approach Empirical evidence from a university hospital was gathered via interviews, internal documents, obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Previous studies have shown middle managers' role in mediating between strategy and day-to-day activities. However, their role in quality improvement project implementation has not yet been described (Zjadewicz et al , 2016; Olsson et al , 2017). In this study, quality gaps and connected improvement proposals by those identified as middle managers are focused on attaining improvements so that the final service results in better value for the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown middle managers' role in mediating between strategy and day-to-day activities. However, their role in quality improvement project implementation has not yet been described (Zjadewicz et al , 2016; Olsson et al , 2017). In this study, quality gaps and connected improvement proposals by those identified as middle managers are focused on attaining improvements so that the final service results in better value for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the traditional approach of inviting contributions from each medical or surgical division may not reveal disconnections between the stages of the process (Ben-Tovim et al, 2008). Finally, this kind of cross-JHOM 34,8 functional process, using a large capacity of the hospital's human and technological resources, has to be managed at macro level by middle and top managers (Castillo et al, 2011;Jweinat et al, 2013;Olsson et al, 2017). Consequently, all the actors in the frontline, middle and top management should be able to capture important aspects of the quality of the service offered.…”
Section: Introductionmentioning
confidence: 99%
“…Collier et al (2004) shared the positive effects of middle managers' involvement based on their perceptions of the firm strategy. This focus on middle managers is consistent with the growing recognition of their key roles in promoting or stifling corporate entrepreneurship efforts (Burgelman, 1983b;Floyd and Woolridge 1992;Huy, 2001;Olsson et al, 2017).…”
Section: The Importance Of Middle-level Managers' Perceptionsmentioning
confidence: 53%
“…By identifying middle managers as strategists, we were able to explore their lived experiences and practices and contribute to the body of knowledge on middle managers in the public sector. Our study bridges the gap that still exists as most of the current studies on the middle manager do not explicitly focus on their strategising role within the public sector in a developing country (Hansell 2018;Jones & Hooper 2017;Joshi & Jha 2017;Lystbaek et al 2017;Livijn 2019;Olsson, Aronsson & Sandberg 2017).…”
Section: Middle Management Perspectivementioning
confidence: 84%